MECHANISM FOR IMPLEMENTING THE PROGRAM FOR SUSTAINABLE DEVELOPMENT OF THE REGION'S ECONOMY WITH THE PREDOMINANCE OF A SEPARATE TYPE OF ECONOMIC ACTIVITY - A. V. Bandurin; I. S. Borisova (Модернизация, инновация, развитие, 2018)
In the article the mechanism of realization of the program of sustainable development of the economy of the region with the predominance of the type of economic activity (PVC) is considered. The procedure for implementing the program for sustainable development of the region's economy was developed with the predominance of a separate type of economic activity: strategic vision, assessing the sufficiency of strategic resources, strategic planning, analyzing the attainability of strategic goals, program decomposition, control and regulation. The functional structure of the dominant type of economic activity in the regional economy and the cybernetic scheme for allocating resources for the sustainable development of the region's economy with PVC are developed. The result of using the simulation model of the sustainable development of the economy of the Lipetsk region for the period until 2020 was adapted. A matrix of mutual influence among the participants of the regional economy on each other and a matrix of opportunities for accessing the competencies of the regional economy to the available resources were constructed. The distribution of resources between competences in the economy of the Lipetsk region is calculated. A mechanism has been created for the implementation of the program for the sustainable development of the region's economy with the predominance of a separate type of economic activity.Purpose: to present the author's mechanism for implementing the program for sustainable development of the region's economy with the predominance of a separate type of economic activity.Methods: the scientific article is based on the provisions of the neoclassical institutional theory, the principles of sustainable development and the basic postulates of the regional economy. The article uses comparative, tabular, graphical and economic-statistical methods.Results: the final form of the mechanism for implementing the program for sustainable development of the region's economy was drawn up with the involvement of the predominant type of economic activity. It has been established that the development of a mechanism for the implementation of the sustainable development program for the region's economy with PVCD implies the use of a "contour-modular" approach in which all the main contours of the management of functional areas are linked within the modules describing the main stakeholder groups. Conclusions and Relevance: the practical significance of the developed mechanism lies in the fact that it can be used in any region. Particular attention should be paid to the information, technical and personnel contours in the process of implementing the sustainable development program for the region's economy, improving the quality of which is carried out using certain economic models that allow us to determine the optimal values of the specific parameters of the state of each of them.